SPECIAL CLOTHING DESIGN FOR HIGH TEMPERATURE OPERATIONS - LIUXI XU; XIN XU; YI WEN (International Journal of Innovations in Engineering Research and Technology, 2021)
The design of special clothing for high temperature operation is studiedin this paper. Under reasonable assumptions, the corresponding mathematical model is established. The differential equation model of heat conduction according to the temperature change of the four garment materials, and the thickness of the material of the second layer is represented by variables is established. And then the differential equation model for four layers cloth is introduced, in which the thickness of the material of the second layer and the fourth layer is regarded as two variables. The optimal thicknesses of the materials of the second layer and the fourth layer are solved, respectively.